IMPLEMENTASI SOFT SKILL DAN MOTIVASI TERHADAP KESIAPAN KERJA PADA SISWA/I SMKN 25 JAKARTA SELATAN - Oktaprianto, Eka; Jusdienar, Akka Latifah; Sambo, Andarias (Journal MISSY (Management and Business Strategy), 2025)
ABSRACT The aim of this research is to see how soft skills and motivation influence the work readiness of class XI students at SMKN 25 South Jakarta. The background to this research is the high unemployment rate of vocational school graduates, which shows that there is a difference between the competence of graduates and the requirements needed by the world of work. Two important factors that are considered to increase students' work readiness are soft skills and motivation. This research uses a quantitative descriptive approach and collects data by distributing questionnaires to 64 people selected through purposive sampling. Structural Equation Modeling (SEM) based on Partical Least Square (PLS) was used to analyze the data. The SmartPLS application is used to do this. The research results show that soft skills and motivation have a positive and significant effect partially and simultaneously on work readiness. This conclusion shows that improving soft skills and work motivation is an effective strategy for preparing vocational school graduates for the competitive world of work. Keywords: Soft Skills1, Motivation2, Work Readiness3